STUDENT LIFESTYLE CHANGE IN THE INDUSTRIAL REVOLUTION 4.0 AT SMA NEGERI 5 KUPANG - Januarius Sabang; Idris (SocioEdu: Sociological Education, 2022)
The purpose of this study was to determine the efforts made by the school in facing the industrial revolution 4.0 at SMA Negeri 5 Kupang. This research uses a qualitative approach. Collecting data using observation, interviews, and documentation. Meanwhile, data analysis was performed interactively by Miles and Huberman. The results showed that the changes in the lifestyles of students in the era of the industrial revolution 4.0 in SMA Negeri 5 Kupang could not be separated from the influence of advances in information and communication technology. Changes in lifestyle in the era of industrial revolution 4.0 between students at SMA Negeri 5 Kupang and the surrounding environment as well as students' absorption of developments that occur globally both in the fields of Science and Technology and Information Technology which are getting stronger which can be seen with the naked eye such as the development of communication tools such as cellphones. The efforts made by the school in facing the industrial revolution 4.0 era are; (1) condition students to accept the form of learning model given from school by online/another way (2) looking for applications that are young to be understood by students so that they can carry out the learning process online (3) motivate students to learn not only knowledge and skills rather, it identifies the source of learning for this knowledge and skills.